Postoperative Hearing Outcomes and Usefulness of Endoscopy-Assisted Tympanoplasty in Pars Tensa Cholesteatoma - Takaomi Kurioka; Kunio Mizutari (International Archives of Otorhinolaryngology)
Introduction In recent years, transcanal endoscopic ear surgery (TEES) has gained widespread recognition as an excellent surgical field for blind spots such as the sinus tympani (ST) when compared to microscopic ear surgery (MES).